Treatment of Closed Tibia Shaft Fractures in Children: A Systematic Review and Meta-Analysis - Stenroos, Antti; Puhakka, Jani; Nietosvaara, Yrjänä; Kosola, Jussi (European Journal of Pediatric Surgery, 2019)
Tibia fractures are among the most common long-bone fractures in children. Despite this, there is no current consensus on the optimal treatment strategy for closed displaced tibia shaft fractures in the pediatric patient population. The aim of this study is to compare the reported complications and outcomes of reduction and cast immobilization versus flexible intramedullary nailing in the treatment of pediatric tibia shaft fractures. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement when conducting and reporting this prospectively registered systematic review. Eleven studies were included. Quality of the studies was assessed using the Coleman methodology score. Mantel–Haenszel cumulative odds ratios were used to compare the risk of complication between different methods of treatment. Eleven studies including 1,083 patients with diaphyseal fractures of the tibia met the inclusion criteria. The most common fracture type was simple 42-A (782; 91%). Majority (75%) of the patients were treated nonoperatively. The total complication rate was higher among operatively treated patients (24 vs. 9%; p < 0.05). Satisfactory fracture alignment had to be restored surgically in 5% of the primarily nonoperatively treated patients. The evidence levels of the included studies were II (1), III (2), and IV (7). Three-fourths of closed diaphyseal fractures of the tibia in children are still treated with reduction and cast immobilization. Flexible intramedullary nailing is associated with significantly higher complication rate than nonoperative treatment.
Keywords: tibia fracture; children; elastic intramedullary nailing of tibia; flexible intramedullary nailing of tibia; pediatric lower leg fractures